Electricity (Dis)Integration? An Analysis of Price Convergence and its Determinants in European Electricity Markets - Kłopecka, Kornelia; Bonar, Dawid (International Journal of Energy Economics and Policy, 2025)
In light of the energy crisis, stricter climate policies, and disruptions from the COVID-19 pandemic and the war in Ukraine, understanding the convergence of electricity prices is essential, as it reflects market integration. This study assesses price convergence in 23 European electricity markets from January 2015 to December 2024 using monthly wholesale day-ahead prices. We employ a novel approach based on the Payne test (Payne et al., 2022), which allows for two structural breaks and accounts for cross-sectional dependence. To further explore the determinants of convergence, we apply clustering methods and logistic regression to assess the influence of cross-border interconnections, national electricity mix structures, and regional characteristics on electricity price dynamics. The findings indicate a persistently low integration of electricity market. Importantly, convergence is not strongly linked to physical interconnections between countries. Instead, differences in the structures of the national electricity mix emerge as more influential. Regional dynamics also play a role, with Northern and Central Western Europe showing greater convergence tendencies. These findings highlight structural obstacles to full market harmonisation and suggest that future policy should focus not only on infrastructure, but also on aligning electricity generation strategies and fostering regional cooperation to support a more integrated electricity market.